Comparison of ultrasonography-guided pectoral nerve block with patient-controlled analgesia for breast surgery patients - Serce, Gokhan İsık; Kucur Tulubas, Evrim (The European Research Journal, 2021)
Objectives: Pectoral nerve block is an effective method that can be applied for analgesic purposes in breast surgery. In this prospective study we aimed to compare the postoperative analgesic efficacy of pectoral nerve block for postoperative analgesia and patient-controlled analgesia (PCA) for patients undergoing breast surgery in terms of the incidence of nausea and vomiting. Methods: The study included 93 patients who underwent ASA I-II anesthesia and breast surgery. Group 1 was PCA group, group 2 was PECS (Pectoral Nerves) block group. PECS block was administered as PECS-1 and PECS-2 block under the guidance of ultrasonography. Patients investigated in the study had postoperative monitoring forms examined for vital signs and visual analog scale (VAS) scores in the 1st, 6th and 24th hours. Results: When the pectoral nerve block with bupivacaine under ultrasound guidance was compared with PCA device, there were significant reductions in VAS score at 24 hours.(1.53 vs 4.27, 1.10 vs 3.27 and 0.90 vs 1.93, respectively; p = 0.0001). Although there was no significant difference in terms of vomiting, there was a difference in favor of pectoral nerve block especially at the postoperative 6th hour in terms of nausea. Conclusions: Pectoral nerve block can be used in the patients undergoing breast surgery due to the lower visual analog score and nausea incidence in the postoperative period.